(untitled) (Revista Cientifica Ingenio Magno, 2021)
Among precipitation-hard enable aluminum alloys, Al-Zn-Mg alloys have been the subject of much research because they are the alloys with the highest mechanical strength. The desirable mechanical properties of this class of alloys are due to structural heterogeneities on a nanoscale, which are formed at an intermediate stage in the evolution of the supersaturated solid solution towards an equilibrium structure, where excessive solute is secreted in the form of incoherent precipitates or Orewa’s mechanism [1]. This work aimed to evaluate the influence of the manufacturing processes: solidification, homogenization / solubilization and aging in the Al 7075 alloy using low cost characterization techniques, such as hardness and microhardness measures. For the conditions studied in this work, it can be concluded that the results of hardness and microhardness have substantial influence depending on the different conditions: crude solidification, solubilized / tempered in water and aged and as received (T6 51), confirming that they can serve as controls during the processing steps. It was also possible to predict the performance limit from the Vickers microhardness results for the different Al 7075 alloy processing conditions, with an error of 5% for the received condition (T6 51).